Economic Impacts of Highway Beautification in Florida - Hayk Khachatryan; Alan W. Hodges; Mohammad Rahmani; Thomas J. Stevens (EDIS)
The Florida Department of Transportation is allocated money every year for highway landscaping projects. They make driving more pleasant and are better for the environment, but do they attract private investment and contribute to the economy? This study, commissioned by the FDOT, finds that the average annual economic impacts of highway beautification expenditures in Florida during 2008–2013 amounted to $46 million in output impacts and $28 million in value-added impacts. This 7-page fact sheet was written by Hayk Khachatryan, Alan W. Hodges, Mohammad Rahmani, and Thomas J. Stevens, and published by the UF Department of Food and Resource Economics, December 2014. http://edis.ifas.ufl.edu/fe963